Learning Sociology Using the Jigsaw Model Using Question Cards - Siti Rahayu (Formosa Journal of Sustainable Research, 2023)
This research aims at explaining the reasons why jigsaw model with quiz card is done to improve students’ achievement in Sociology and providing an overview on what teachers did toward improving students’ achievement and responsibility using jigsaw and quiz card significantly. The subject was 34 students of XI IPS 3 in SMA Negeri 1 Pundong. To collect data, observation sheet, interview, test, and documentation were used. Data validation and collection were done during the teaching and learning process. The data were described quantitively in percentage and qualitatively using interactive model. The result shows that most of the students (94,18%) passed the minimum criteria on cognitive aspects with 86,14% average of achievement. The psychomotor aspects even achieve 100% of students with average of 87,19 %